Selected Areas in Cryptography: 27th International Conference, Halifax, NS, Canada (Virtual Event), October 21-23, 2020, Revised Selected Papers - Dunkelman, Orr; Jacobson, Michael J., Jr; O'Flynn, Colin (Lecture Notes in Computer Science, 2021)
This book contains revised selected papers from the 27th International Conference on Selected Areas in Cryptography, SAC 2020, held in Halifax, Nova Scotia, Canada in October 2020. The 27 full papers presented in this volume were carefully reviewed and selected from 52 submissions. They cover the following research areas: design and analysis of symmetric key primitives and cryptosystems, including block and stream ciphers, hash functions, MAC algorithms, and authenticated encryption schemes, efficient implementations of symmetric and public key algorithms, mathematical and algorithmic aspects of applied cryptology, and secure elections and related cryptographic constructions